Separate value comparison and learning mechanisms in macaque medial and lateral orbitofrontal cortex. - Noonan, M; Walton, M; Behrens, T; Sallet, J; Buckley, M; Rushworth, M (2010)
Uncertainty about the function of orbitofrontal cortex (OFC) in guiding decision-making may be a result of its medial (mOFC) and lateral (lOFC) divisions having distinct functions. Here we test the hypothesis that the mOFC is more concerned with reward-guided decision making, in contrast with the lOFC's role in reward-guided learning. Macaques performed three-armed bandit tasks and the effects of selective mOFC lesions were contrasted against lOFC lesions. First, we present analyses that make it possible to measure reward-credit assignment--a crucial component of reward-value learning--independently of the decisions animals make. The mOFC lesions do not lead to impairments in reward-credit assignment that are seen after lOFC lesions. Second, we examined how the reward values of choice options were compared. We present three analyses, one of which examines reward-guided decision making independently of reward-value learning. Lesions of the mOFC, but not the lOFC, disrupted reward-guided decision making. Impairments after mOFC lesions were a function of the multiple option contexts in which decisions were made. Contrary to axiomatic assumptions of decision theory, the mOFC-lesioned animals' value comparisons were no longer independent of irrelevant alternatives.